Static and dynamic analyses of traditional Chinese timber columns under horizontal accelerations. (January 2023) - An, Renbing; You, Wenlong; Pan, Yi; Fan, Yuanqing
Abstract: Traditional Chinese timber columns are prone to rocking and sliding because the column feet are directly placed on foundation stones. Determining the motion of columns under horizontal accelerations is essential to preventing the collapse of traditional Chinese timber structures during earthquakes. This paper divides the states of motion of traditional Chinese timber columns into static and dynamic. For the static state, a coefficient describing the compression height is proposed based on the variation of the compressive zone at the column foot, and the moment-rotation relationship of the column foot is then established. For the dynamic state, the rocking and slide-rocking dynamic equations are proposed by considering the contribution of the column foot and the mortise-tenon joint to the lateral force of the timber columns. Finite element models of timber frames are constructed and validated through existing timber frame shaking table tests. Based on numerical simulation, this paper analyzed 125 groups of timber column models and 98 groups of timber frame models to validate the proposed static and dynamic equations. The results reveal that the proposed moment-rotation relationship of the column foot agreed with the simulated results at the initial stiffness and bearing capacity. Hence, the proposed dynamic equations reflect the timber columns' slide and rocking characteristics under horizontal acceleration. This investigation provides a theoretical base for the reinforcement and protection of traditional Chinese timber structures during earthquakes.